Signs of enhanced sleep and sleep-associated memory processing following the anti-inflammatory antibiotic minocycline in men. (February 2017) - Besedovsky, Luciana; Schmidt, Eva-Maria; Linz, Barbara; Diekelmann, Susanne; Lange, Tanja; Born, Jan
Pro-inflammatory cytokines can promote sleep and neuronal processes underlying memory formation. However, this has mainly been revealed in animal studies. In this double-blind, placebo-controlled within-subject designed study, we examined how changes in the balance between pro- and anti-inflammatory signalling affect sleep and sleep-associated memory consolidation in humans. After learning declarative memory tasks (word pairs, texts) and a procedural memory task (finger tapping) in the evening, 21 healthy young men orally received either 200 mg of the anti-inflammatory antibiotic minocycline or placebo shortly before nocturnal sleep. Sleep was allowed between 23:00 and 07:00 h and recorded polysomnographically. Retrieval of memories was tested two days later. Because of outliers or missing data, final sample size was reduced to n = 14–19. Our data suggest that rather than weakening sleep as expected based on animal studies, the anti-inflammatory agent promoted sleep and memory consolidation. Specifically, minocycline increased slow-wave activity (0.68–4.0 Hz) during non-rapid eye movement sleep stage 2 and selectively enhanced episodic aspects in memory (i.e. memory for the temporal order of events in the texts). In combination with previous results, our findings indicate that, in humans, reducing pro-inflammatory signalling can act towards deepening non-rapid eye movement sleep and enhancing its memory forming efficacy.